PENINGKATAN KETERAMPILAN WIRAUSAHA SANTRI DI PONDOK PESANTREN HIDAYATULLAH MELALUI BUDIDAYA IKAN NILA SISTEM BIOFLOK - Munaeni, Waode; Abdullah, Nursanti; Haji, Sulfi Abdul; Syafari, Muhamad Rismon (Abdi Panca Marga, 2024)
Tahfidz Qur'an Hidayatullah Gambesi Islamic Boarding School is an Islamic boarding school that supports skill development in the field of entrepreneurship, such as tilapia cultivation. However, the obstacles faced are low production yields, very high feed costs, and the lack of knowledge and skills of students in fish farming. The aim of this activity is to improve skills in cultivating tilapia using the biofloc system and marketing the cultivation products to students. This activity will be carried out from July to October 2023 at the Tahfidz Qur'an Hidayatullah Gambesi Islamic Boarding School, Ternate City, North Maluku. The activity stages include: providing a complete set of cultivation tools; training and assistance in biofloc system tilapia cultivation; feed management; water quality; and marketing production results. Data collection techniques through questionnaires were given to students before and after training and providing material. The training participants consisted of 17 junior high school (SMP) students in grades 2 and 3. The results of the activity showed that there was an increase in the knowledge and skills of students at the Tahfidz Qur'an Hidayatullah Islamic Boarding School regarding tilapia cultivation using the biofloc system by 71%. The results of this activity also show that students are interested in developing a biofloc system for tilapia cultivation. It is hoped that this activity can increase students' entrepreneurial interest, increase tilapia fish production, and become an example for other Islamic boarding schools in North Maluku. References Avnimelech, Y. (2012). Biofloc technology-a practical guide book (2nd ed.). Baton Rouge, LA (USA): The World Aquaculture Society. BPPP [Balai Pelatihan dan Penyuluhan Perikanan] Kota Ternate. 2021. Profil Kelompok Perikanan, Kelompok Usaha Bersama 02. Badan Riset dan SDM Kelautan dan Perikanan, Kementerian Kelautan dan Perikanan. Chalik A. 2022. Hasil Budidaya Tanaman Santri Ponpes Hidayatullah Gambesi Disambut Gembira. Di unduh dari: https://hidayatullah.or.id/hasil-budidaya-tani-santri-ponpes-hidayatullah-gambesi-disambut-gembira/ tanggal 27 Maret 2023. Dauda, A. B., Ajadi, A., Tola-Fabunmi, A. S., & Akinwole, A. O. (2019). Waste production in aquaculture: Sources, components and managements in different culture systems. Aquaculture and Fisheries, 4, 81–88. https://doi.org/10.1016/j.aaf.2018.10.002. Emerenciano, M. G. C., Martínez-Córdova, L. R., Martínez-Porchas, M., & Miranda-Baeza, A. (2017). Biofloc Technology (BFT): A Tool for Water Quality Management in Aquaculture. In Water Quality. InTech. https://doi.org/10.5772/66416 Google Maps. (2023). Peta Jarak Lokasi Pondok Pesantren Tahfidz Qur’an Hidayatullah dengan Universitas Khairun. Hisano, H., Parisi, J., Cardoso, I. L., Ferri, G. H., & Ferreira, P. M. F. (2019). Dietary protein reduction for Nile tilapia fingerlings reared in biofloc technology. Journal of the World Aquaculture Society, 1–11. https://doi.org/10.1111/jwas.12670. Kurniawan, A., & Asriani, E. (2016). Aplikasi Kolam Bundar dan Bioflok pada Pembesaran Ikan Lele di Kelompok Remaja Masjid Paritpadang, Sungailiat, Bangka. Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 3(2), 53–60. Luo, G., Gao, Q., Wang, C., Liu, W., Sun, D., Li, L., & Tan, H. (2014). Growth, digestive activity, welfare, and partial cost-effectiveness of genetically improved farmed tilapia (Oreochromis niloticus) cultured in a recirculating aquaculture system and an indoor biofloc system. Aquaculture, 422–423, https://doi.org/10.1016/j.aquaculture.2013.11.023 Marisda, D. H., Anisa. (2019). Penerapan teknologi bioflok budidaya ikan nila untuk pemanfaatan pekarangan rumah nonproduktif. Sewagati, 3(3),78–84. Millah, D. (2015). Audience centered pada metode presentasi sebagai aktualisasi pendekatan student centered learning. Edukasia: Jurnal Penelitian Pendidikan Islam, 10(2), 255–278. Avnimelech, Y. (2012). Biofloc technology-a practical guide book (2nd ed.). Baton Rouge, LA (USA): The World Aquaculture Society. BPPP [Balai Pelatihan dan Penyuluhan Perikanan] Kota Ternate. 2021. Profil Kelompok Perikanan, Kelompok Usaha Bersama 02. Badan Riset dan SDM Kelautan dan Perikanan, Kementerian Kelautan dan Perikanan. Chalik A. 2022. Hasil Budidaya Tanaman Santri Ponpes Hidayatullah Gambesi Disambut Gembira. Di unduh dari: https://hidayatullah.or.id/hasil-budidaya-tani-santri-ponpes-hidayatullah-gambesi-disambut-gembira/ tanggal 27 Maret 2023. Dauda, A. B., Ajadi, A., Tola-Fabunmi, A. S., & Akinwole, A. O. (2019). Waste production in aquaculture: Sources, components and managements in different culture systems. Aquaculture and Fisheries, 4, 81–88. https://doi.org/10.1016/j.aaf.2018.10.002. Emerenciano, M. G. C., Martínez-Córdova, L. R., Martínez-Porchas, M., & Miranda-Baeza, A. (2017). Biofloc Technology (BFT): A Tool for Water Quality Management in Aquaculture. In Water Quality. InTech. https://doi.org/10.5772/66416 Google Maps. (2023). Peta Jarak Lokasi Pondok Pesantren Tahfidz Qur’an Hidayatullah dengan Universitas Khairun. Hisano, H., Parisi, J., Cardoso, I. L., Ferri, G. H., & Ferreira, P. M. F. (2019). Dietary protein reduction for Nile tilapia fingerlings reared in biofloc technology. Journal of the World Aquaculture Society, 1–11. https://doi.org/10.1111/jwas.12670. Kurniawan, A., & Asriani, E. (2016). Aplikasi Kolam Bundar dan Bioflok pada Pembesaran Ikan Lele di Kelompok Remaja Masjid Paritpadang, Sungailiat, Bangka. Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 3(2), 53–60. Luo, G., Gao, Q., Wang, C., Liu, W., Sun, D., Li, L., & Tan, H. (2014). Growth, digestive activity, welfare, and partial cost-effectiveness of genetically improved farmed tilapia (Oreochromis niloticus) cultured in a recirculating aquaculture system and an indoor biofloc system. Aquaculture, 422–423, 1–7. https://doi.org/10.1016/j.aquaculture.2013.11.023 Marisda, D. H., Anisa. (2019). Penerapan teknologi bioflok budidaya ikan nila untuk pemanfaatan pekarangan rumah nonproduktif. Sewagati, 3(3),78–84. Millah, D. (2015). Audience centered pada metode presentasi sebagai aktualisasi pendekatan student centered learning. Edukasia: Jurnal Penelitian Pendidikan Islam, 10(2), 255–278. Munaeni, W., Aris, M., Darsan, I. M., Labenua, R., Disnawati. (2022a). Sosialisasi dan pelatihan teknologi budidaya ikan nila sistem bioflok pada Kelompok Usaha Bersama. Jurnal Abdi Insani, 9(4), 1830–1838. https://doi.org/10.29303/abdiinsani.v9i4.797 Munaeni, W., Aris M., Haji, S.A. (2022b). Usaha budidaya ikan nila sistem bioflok di Kelurahan Fitu Kecamatan Ternate Selatan Maluku Utara. Jurnal Pengabdian kepada Masyarakat Nusantara (JPkMN). 3(2): 660–668. https://ejournal.sisfokomtek.org/index.php/jpkm/article/view/413 Munaeni, W., Aris, M., Labenua, R. (2023). Pelatihan aplikasi probiotik melalui pakan pada pembudidaya ikan nila di keramba jaring apung Danau Ngade. JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 4(2), 212-220. Soeprapto, H., Ariadi, H., Khasanah, K. (2022). Pelatihan pembuatan probiotik herbal bagi kelompok pembudidaya ikan. J-ABDI: Jurnal Pengabdian kepada Masyarakat, 1(8), 1929–1934. Suheri. (2018). Makna interaksi dalam komunikasi (teori interaksi simbolik dan teori konvergensi simbolik). Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 9(2), 52–63. https://doi.org/10.32505/hikmah.v9i2.1739. Wei, Y., Liao, S. A., & Wang, A. L. (2016). The effect of different carbon sources on the nutritional composition, microbial community and structure of bioflocs. Aquaculture, 456, 88–93. https://doi.org/https://doi.org/10.1016/j.aquaculture.2016.08.040